A computational framework to support probabilistic criticality modelling for the geological disposal of radioactive waste - E. Adam Paxton; Jiejie Wu; Tim Hicks; Slimane Doudou; David Applegate; Robert Mason; Andrew Price; Liam Payne (Annals of Nuclear Energy, 2025)

Effects of human footprint and biophysical factors on the body‐size structure of fished marine species - Nestor E. Bosch; Jacquomo Monk; Jordan Goetze; Shaun Wilson; Russell C. Babcock; Neville Barrett; Jock Clough; Leanne M. Currey‐Randall; David V. Fairclough; Rebecca Fisher; Brooke A. Gibbons; David Harasti; et al. (Conservation Biology, 2022)
Marine fisheries in coastal ecosystems in many areas of the world have historically removed large‐bodied individuals, potentially impairing ecosystem functioning and the long‐term sustainability of fish populations. Reporting on size‐based indicators that link to food‐web structure can contribute to ecosystem‐based management, but the application of these indicators over large (cross‐ecosystem) geographical scales has been limited to either fisheries‐dependent catch data or diver‐based methods restricted to shallow waters (

Carbon on the Northwest European Shelf: Contemporary Budget and Future Influences - Oliver Legge; Martin Johnson; Natalie Hicks; Tim Jickells; Markus Diesing; John Aldridge; Julian Andrews; Yuri Artioli; Dorothee C. E. Bakker; Michael T. Burrows; Nealy Carr; Gemma Cripps; et al. (Frontiers in Marine Science, 2020)

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)